Magnetotelluric evidence of the tectonic boundary between the Río de La Plata Cratón and the Pampean terrain (Chaco-Pampean Plain, Argentina): the extension of the Transbrasiliano Lineament - Peri, Verónica Gisel (2013)
The Transbrasiliano Lineament represents a continental shear belt that transversely intersects the South American Platform from NNE to SSW. Much evidence of this lineament exists to the north, but it remains uncharacterized in the distal Andean foreland to the south, where it is associated with the tectonic boundary between the Río de la Plata Craton and the Pampean terrane. This tectonic boundary is mostly unexposed in the Chaco-Pampean Plain (Argentina). Debate continues about the existence of an east- or west-dipping subduction zone and a later collisional event between the terranes. Here, we report the results of a magnetotelluric survey along a W?E profile at 27° S between 63° 45′ and 60° 30′ W. To characterize the geoelectric structure, the magnetotelluric data were processed, the dimensionality and distortion of the geoelectrical medium were analyzed, and a 2-D inversion model was developed. The distribution of the resistivities at the lithospheric scale indicates a highly resistive crust (20,000 Ω m) on the east side of the profile that is correlated with the Río de La Plata Craton. On the west side of the profile, a less resistive but still highly resistive crust (12,000 Ω m) is correlated with the Pampean terrane. The highly resistive blocks are separated by an east-dipping conductive anomaly (150?250 Ω m) that is correlated with the Transbrasiliano Lineament. This conductive feature is consistent with the east-dipping subduction model and can be explained by the presence of graphite in paleosutures in long-stable geological terranes. Oblique convergence between the terranes may have developed the transpressional shear belt. The results provide new geophysical evidence of the tectonic boundary between the Río de La Plata Craton and the Pampean terrane beneath the Chaco-Pampean Plain that extends southward into the Transbrasiliano Lineament. The study also improves the knowledge of the amalgamation of Western Gondwana.